COVID-19 outbreak in an urban indigenous community in Northern Lima, Peru - Llanos Zavalaga, Luis Fernando (2022)
Populations that live in poverty with restricted social mobility and limited access to health care services, such as the Shipibo-Konibo community of Cantagallo (Rimac), are at risk to get COVID-19. After the report of three fatalities due to COVID-19 in that community a multidisciplinary team involving the ministries of health, interior affairs, culture and the major of the Rimac district, the community of that district and NGOs did not allow the movement of persons in and out the community. The proportion of members of the community with positive IgM serological tests come down and those with positive IgG levels increased, suggesting reduced transmission or presence of mild- asymptomatic cases. The vulnerability of indigenous communities as reported here is a clear evidence of the need to have sustainable and articulated plans to protect these communities from devastating diseases such as COVID-19.